2021
DOI: 10.1136/bmjdrc-2021-002451
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical profile of 786 sequential episodes of diabetic ketoacidosis in adults with type 1 and type 2 diabetes mellitus

Abstract: IntroductionWe explored the clinical and biochemical differences in demographics, presentation and management of diabetic ketoacidosis (DKA) in adults with type 1 and type 2 diabetes.Research design and methodsThis observational study included all episodes of DKA from April 2014 to September 2020 in a UK tertiary care hospital. Data were collected on diabetes type, demographics, biochemical and clinical features at presentation, and DKA management.ResultsFrom 786 consecutive DKA, 583 (75.9%) type 1 diabetes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…This likely contributed to the more extended hospital stay, increased admission to the intensive care unit, and a 7-fold increase in mortality in patients with T2DM, consistent with previous studies (33)(34)(35)(36)(37). Thus, Ooi and colleagues found a similar clinical presentation and disease severity between patients with T1DM and T2DM hospitalized with DKA but with a more extended hospital stay in patients with T2DM (33). Several studies have found a higher inpatient mortality in patients with DKA and T2DM than T1DM (14,35,36), which may be attributed to older age and more comorbidities in patients with T2DM (33).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This likely contributed to the more extended hospital stay, increased admission to the intensive care unit, and a 7-fold increase in mortality in patients with T2DM, consistent with previous studies (33)(34)(35)(36)(37). Thus, Ooi and colleagues found a similar clinical presentation and disease severity between patients with T1DM and T2DM hospitalized with DKA but with a more extended hospital stay in patients with T2DM (33). Several studies have found a higher inpatient mortality in patients with DKA and T2DM than T1DM (14,35,36), which may be attributed to older age and more comorbidities in patients with T2DM (33).…”
Section: Discussionsupporting
confidence: 89%
“…Non-adherence to diabetes therapy and infection were the most common precipitating causes for hospitalization for DKA in our cohort. Non-adherence to insulin was the most typical cause for DKA in patients with T1DM, while infection was the leading cause in patients with T2DM, which is consistent with other studies (11,(33)(34)(35)(36)(37)(38)(39). Since recurrent DKA is associated with increased morbidity and mortality, identifying precipitating factors is key to the long-term management of patients with DKA.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Diabetic ketoacidosis (DKA) is the most common acute hyperglycemic emergency in people with diabetes mellitus (DM) [ 1 ]. This potentially life-threatening complication can occur in both type 1 and type 2 DM, and it can be associated with significant morbidity and increased length of hospital stay [ 2 , 3 ]. Mortality rates in DKA patients have fallen significantly in the past 20 years to <1% [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%